Peran Sosialisasi Pendidikan Ketamansiswaan dalam Pembentukan Karakter Bangsa - Saryanto Saryanto; Rahayu Retnaningsih; Atikah Nur ‘aini; Bintang Adi Saputra; Emliana Bnani Amlupu; Febri Irwanda; Fina Alfianita; Laila Syakila; Lugi Priyanto; Olivia Nurwahyuningsih; Raden Muhammad Yusuf; Retna Muriana; Resmiyati Resmiyati; Tri Laili (Lembaga Pengembangan Kinerja Dosen, 2024)
In the formation of the nation's character, it is necessary to teach ketamansiswaan education to apply inclusive and national-based educational values, especially in education in Indonesia. The team of lecturers and fellow students of Padepokan 47 Real Work Lecture of Sarjanawiyata Tamansiswa University conducted community service on the role of socialization of ketamansiswaan education in the formation of national character at SD Negeri 1 Ngandong. The purpose of this socialization is so that the community, especially teachers and employees of SD Negeri 1 Ngandong, can find out how the role of ketamansiswaan education in the formation of national character through the teachings of Tamansiswa.To achieve these activities, socialization activities have been carried out in the first week at SD Negeri 1 Ngandong regarding the socialization of ketamansiswaan education in the formation of national character. The implementation of this socialization begins with planning followed by the presentation of material fundamentally to the main discussion. This socialization activity is expected to be useful and for teachers and employees as well as at SD Negeri 1 Ngandong and fellow students of the Real Work Lecture Padepokan 47 Sarjanawiyata Tamansiswa university. This socialization is expected to provide knowledge in overcoming problems regarding the lack of understanding of the teachings of Tamansiswa education.